2000
DOI: 10.1016/s0022-2275(20)32021-6
|View full text |Cite
|
Sign up to set email alerts
|

Increase in fragmented phosphatidylcholine in blood plasma by oxidative stress

Abstract: Oxidatively modified phospholipids with fragmented acyl chains have attracted much interest because of their proinflammatory activity and their potential involvement in atherosclerosis. They can be formed in vitro by free radical treatment of unsaturated phospholipids but it is not known under which conditions they accumulate in vivo. We assayed one species of fragmented phosphatidylcholine (PC) in human blood plasma by high performance liquid chromatography after precolumn derivatization with chloromethylanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(16 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…However, their concentrations decreased gradually and at 30 days after reperfusion differences reached statistically significant levels ( Table 3 ; Figure 3B ). In a study by Frey et al ( 23 ), levels of an unknown fragmented OxPC, which was measured in 5 patients undergoing coronary artery bypass grafting using liquid chromatography (after precolumn derivatization) showed a significant increase after 3 h reperfusion compared with baseline values. However, as they did not use a mass spectrometry approach, they were not able to identify the exact structure of the compound in question.…”
Section: Discussionmentioning
confidence: 98%
“…However, their concentrations decreased gradually and at 30 days after reperfusion differences reached statistically significant levels ( Table 3 ; Figure 3B ). In a study by Frey et al ( 23 ), levels of an unknown fragmented OxPC, which was measured in 5 patients undergoing coronary artery bypass grafting using liquid chromatography (after precolumn derivatization) showed a significant increase after 3 h reperfusion compared with baseline values. However, as they did not use a mass spectrometry approach, they were not able to identify the exact structure of the compound in question.…”
Section: Discussionmentioning
confidence: 98%
“…Smoking changes the phospholipid composition and decreases the PC content of platelet membranes, 18 which can be important for the blood coagulation reaction. 36 Smoking also causes oxidative stress, 37 leading to fragmentation of PC, 17 which has been associated with atherosclerosis. 38 Considering that PC constitutes the largest pool of choline, it is plausible that these effects of smoking would also alter plasma choline levels, and to some extent be responsible for the diverging associations.…”
Section: Possible Pathomechanismsmentioning
confidence: 99%
“…15 Smokers have higher dietary intake 16 but lower plasma levels of choline. 5 Further, smoking is associated with numerous effects on phospholipid metabolism [17][18][19] and is a major risk factor of CVD. 20 Thus, there may be an interrelationship between smoking, choline metabolism, and the risk of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of PAFAH2 in EC rescued particulate matter-or inflammatory cytokines-induced endothelial barrier disruption, while pharmacological inhibition of PAFAH2 worsened lung injury in TNF-a-challenged mice (75,79). A few other studies have also reported the presence of higher levels of truncated OxPLs in aged mice (80,81), and increased production of fragmented phosphatidylcholine in human blood plasma as well as higher levels of ester-linked but lower level of ether-linked phosphatidylcholine in aged human individuals (82,83). The changes in the levels of lipid profile of ester-vs ether-linked with aging has been attributed as a potential risk factor for the development of various diseases in elderly population.…”
Section: Oxpls In Endothelial Dysfunction-derived Lung Diseasesmentioning
confidence: 94%